Implementation of Business Sustainability Principles on Coffee Shop Business District - Purwadi, Muhammad Guntur; Djatmika , Ery Tri; Handayati , Puji (Profesional Muda Cendekia Publishing, 2024)
This is a qualitative study investigates the business sustainability in Sudimoro Coffee Business District at Malang City from EGSEE aspect and principles of business sustainability. Interviews with senior staff, managers, customers, local government representatives, and business professionals are used to collect data. Customers, managers, and owners of coffee shops are examples of key informants. Comprehensive interviews with top staff members and clients validate assertions made by company proprietors. Local government representatives and a business professional with a comparable background in the field are examples of comparative data.